ANALISIS INTERAKSI STRUKTUR GELOMBANG PADA ANJUNGAN LEPAS PANTAI - Wisafri
Drag coefficient (Cd) and inertia coefficient (Cm) are the coefficients used in Morison Equation to determine structure response. Commonly the coefficients value is taken based on several assumptions or cross-section shape factor of structure, in order to make a vigorous design or other needs took coefficients based on assumptions don't show actual conditions on the field. Hence, Cd and Cm coefficients are computed based on a measurement on the field where the subject of this research is one of UA-STS platforms. The measurements including wave elevations such as time histories and time histories of structure accelerations. The coefficient of Cd and Cm is computed using Morison Equation, and determined this coefficient need are: force, water particle velocity and water particle accelaration. Time histories of structure accelerations are used to solve structure displacements by integralized the acceleration twice against time, so that from the displacements can be reach the force of structure (f). Time histories of wave elevations is used to find water particle velocity (u) and water particle accelerations (u), substitute the value of f, u, and u into Cd and Cm equations, hence results of coefficients UA-STS find are: Cd in X axis = 1.143 CdinYaxis= 1.112 Co, in X axis = 1.049 C. in Y axis = 1.095